2015
DOI: 10.1055/s-0035-1566305
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hormonal Changes on Audiologic Examination in Normal Ovarian Cycle Females: An Analytic Study

Abstract: Introduction There is only limited information from previous studies that suggest that auditory function may be influenced by hormones. Recent advances in the field have exposed the potential role of hormones in modulating the auditory system. Objective This study aims to investigate the relationship between menstrual cycle and outer hair cell function with audiological examination. Methods This is an analytic study with a cross-sectional design. The sampling was a systematic random sampling. We found 49 women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The probable reason for not obtaining a statistically significant difference in suppression across different phases of menstrual cycle could be the small sample size chosen for the study and also the reason that hormones had very less or no effect on the efferent auditory pathway. Similar studies were carried out by Arruda & Silva in 2008 5 and Adriztina in 2016 19 which revealed the same results as their study says that there is no statistical significance in suppression values that they obtained across different phases of menstrual period or menstruation.…”
Section: Resultssupporting
confidence: 79%
“…The probable reason for not obtaining a statistically significant difference in suppression across different phases of menstrual cycle could be the small sample size chosen for the study and also the reason that hormones had very less or no effect on the efferent auditory pathway. Similar studies were carried out by Arruda & Silva in 2008 5 and Adriztina in 2016 19 which revealed the same results as their study says that there is no statistical significance in suppression values that they obtained across different phases of menstrual period or menstruation.…”
Section: Resultssupporting
confidence: 79%
“…Elimination of gonadal steroid hormones via surgical gonadectomy abolishes-and E 2 -replacement re-establishes-an innate relative protection from PTSinducing noise in adult female mice in comparison to males. Additional evidence in humans demonstrating changes in hearing sensitivity and DPOAE amplitudes in preand post-menopausal women also implicate activational effects of E 2 -signaling in the modulation of auditory physiology [76,77].…”
Section: Discussionmentioning
confidence: 91%
“…Some animal and human studies have demonstrated that women may be protected against hearing loss because of estrogen and its signaling pathways [ 86 , 87 ]. Several clinical reports have observed that the level of estrogen and its derivatives positively influence OAE amplitudes and ABR wave latencies [ 88 , 89 , 90 , 91 , 92 ]. Women had subtle fluctuating auditory thresholds during their menstrual cycle phases and their best hearing thresholds were observed at the highest peak of estrogen level [ 92 ].…”
Section: How Could Hormones Influence Hearing In Molecular Aspects?mentioning
confidence: 99%
“…Several clinical reports have observed that the level of estrogen and its derivatives positively influence OAE amplitudes and ABR wave latencies [ 88 , 89 , 90 , 91 , 92 ]. Women had subtle fluctuating auditory thresholds during their menstrual cycle phases and their best hearing thresholds were observed at the highest peak of estrogen level [ 92 ]. Meanwhile, a more extensive scale study including 1830 postmenopausal women found the association between hearing loss and the serum estradiol level [ 93 ].…”
Section: How Could Hormones Influence Hearing In Molecular Aspects?mentioning
confidence: 99%